Kontribusi agama islam sebagai terapi kesehatan tubuh - Putri, Eka Listya (Maliki Interdisciplinary Journal, 2025)
Islam has an important role in human life on this earth, because all Islamic teachings permeate all aspects of human life, one of which is that Islam pays great attention to health issues. A series of worships in Islam can be a medicine and therapy to overcome health problems in the body. A series of worships such as prayer, fasting, Islamic studies, reading the Qur'an, and dhikr have positive impacts that can support physical and spiritual health. Health therapy by performing a series of worships has many benefits and has been proven to be able to restore various health problems and accelerate the healing process of diseases. Movements in prayer that can improve blood circulation. Fasting is often recommended by doctors as a health therapy, Islamic studies that can improve mental health, reading the Qur'an that can relax blood pressure and dhikr that can cure diseases. This journal aims to describe the contribution of Islam to body health by carrying out and implementing the benefits of a series of worships. The implications of this application, it is hoped that all Muslims understand that Islam is involved in maintaining and restoring health in the body so that it can minimize indifference and trivialization of the series of worships.